Efektifitas Mendengarkan Musik Saat Jogging Terhadap Mood Mahasiswa Olahraga - Tasya Fatimah; Herman Subarjah; Mohammad Zaky (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The aim of this research is to examine the impact of listening to music while jogging. The method used in this research is a Causal Comparative research design. Where the sample population in this study was sports students, totaling 100 people and divided into two groups, namely a group that was given treatment and one group that did not receive treatment and functioned as a control or comparison group. The mood instrument used is The Brunnel Mood Scale (BRUMS) developed by Peter C Terry (2010). From the results of the Independent sample t-test, the resulting p-value is 0.00, this value is smaller than the significance level of 0.05, which means there is a significant difference between the Mood value of listening to music and those who don't listen to music.